ANALISIS DESKRIPTIF KINERJA KEUANGAN BPRS BANDAR LAMPUNG BERDASARKAN INDIKATOR CASH RATIO, FDR, BOPO, ROA, NPF, DAN KPMM - Huda Pangestu; Eki Tiyas Nurulia; Noorikha Pandayahesti Saputeri (JOURNAL ISLAMIC ECONOMICS AD DIWAN, 2026)
This study aims to analyze and describe the financial performance of the Islamic Rural Bank (BPRS) Bandar Lampung, based on six key financial ratios: Cash Ratio (CR), Financing to Deposit Ratio (FDR), Operating Expenses to Operating Income (BOPO), Return on Assets (ROA), Non-Performing Financing (NPF), and Minimum Capital Adequacy Requirement (KPMM). BPRS financial performance analysis is crucial for assessing the health, efficiency, and sustainability of Islamic bank operations, particularly during the post-pandemic transition period (2021–2024). This study uses a qualitative approach with a descriptive approach. The data used are secondary data in the form of the annual financial reports of PT. BPRS Bandar Lampung for the 2021–2024 period, as well as publications from the Financial Services Authority (OJK). The data analysis technique employed is qualitative descriptive analysis, encompassing data reduction, data presentation, and drawing conclusions based on comparisons of ratio values with OJK regulatory standards and Islamic banking theory. The results of this descriptive analysis are expected to provide a comprehensive overview of bank financial performance trends and serve as a basis for BPRS management in making strategic decisions to improve efficiency, financing quality, and capitalization